Mimicking codes of death in poetry of the russian satirical drama at the second half of the XIX centure - Irina Andreevna Babenko (Наука. Инновации. Технологии, 2022)
The article deals with the inclusion codes of death in poetry of the satirical plays Saltykov-Shchedrin and Sukhovo-Kobylin. The author, on the basis of textual research dramas concluded that satirical interpretation of the theme of death is an important part of the grotesque poetry plays. The transformation of the traditional notions of the grotesque images antinomy mortalnyh codes outlook due to the peculiarities of playwrights, and changing social and cultural patterns, as reflected in the dramas.